THE UNKNOWN RESEARCHER OF THE CAUCASUS: LYUDMILA FILIPPOVNA VINOGRADOVA (1904-1985) - Gulaeva, Evgenia Ur'evna (History, Archeology and Ethnography of the Caucasus, 2021)
The article is dedicated to Lyudmila Filippovna Vinogradova (1904-1985) – a member of the State Museum of Ethnography of the Peoples of the USSR (currently the Russian Museum of Ethnography), who worked at the Department of the Peoples of the Caucasus since the end of 1930s until the early 60s. The author attempts to shed light on the previously unknown pages in the history of the Caucasian and museum studies in Russia. The objectives of the work include the study of Vinogradova’s professional biography in the context of the history of the State Museum of Ethnography (in particular, the period of the Great Patriotic War) and a review of sources on ethnography and the history of the peoples of the Caucasus made by Lyudmila Filippovna (clothing and photo collections, field reports and diaries). The key materials for the study are archival documents stored in the Russian Museum of Ethnography. The collecting work and scientific profile of Vinogradova in the ethnography of the Ossetians and the peoples of Dagestan (partly Georgia) were due to the need of creating expositions and exhibitions. Over the 25-year period of her activity, the researcher conducted seven ethnographic expeditions (in 1939, 1948 and 1949 in Ossetia, in 1947 in Belarus, in 1955 in Georgia, in 1956 and 1957 in Dagestan); in addition to the reports and field journals, 16 clothing collections (about 250 items) preserved, more than 8000 items and photographs have been registered. Most of these items have not yet been introduced into science. Without knowledge of the biography of the collector and researcher, a comprehensive scientific criticism of sources is impossible – which also applies to Lyudmila Filippovna’s materials. At the same time, the items and photographs she collected, field reports and journals are also an integral part of the story of her life.